Effect of physical exercise using α-lipoic acid (ALA) and eicosapentaenoic acid (EPA) on physical fitness, recovery, and performance in young weightlifters - Jabbar Abd , Hayder (SPORT TK-EuroAmerican Journal of Sport Sciences, 2023)
The purpose of this study was to determine the effect of physical exercise using α-lipoic acid (ALA) and eicosapentaenoic acid (EPA) on physical fitness, recovery, and performance in young weightlifters. The design of the study was experimental. A total of 30 volunteer weightlifters took part in the study, which employed the random partition method. After taking their pre-measurements (height and weight), exercises were created to develop the components of physical fitness, and supplementation was provided for a duration of ten weeks to examine its impact on the other research variables, and the outcomes of the pre arithmetic means were compared. The two methods of homogeneity and equivalence were applied for the data of the research samples. Eicosapentaenoic acid (EPA), which lessens pain and helps the body restore its normal state, was favored by the second experimental group, where the values of the studied variables were better than in the other groups. Finally, α-lipoic acid (ALA) was crucial for recovery by 20% compared to conventional approaches.